1994
DOI: 10.1007/bf00583907
|View full text |Cite
|
Sign up to set email alerts
|

RecA, Tus protein and constitutive stable DNA replication inEscherichia coli rnhA mutants

Abstract: Constitutive stable DNA replication (cSDR), which uniquely occurs in Escherichia coli rnhA mutants deficient in ribonuclease HI activity, requires RecA function. The recA428 mutation, which inactivates the recombinase activity but imparts a constitutive coprotease activity, blocks cSDR in rnhA mutants. The result indicates that the recombinase activity of RecA, which promotes homologous pairing and strand exchange, is essential for cSDR. Despite the requirement for RecA recombinase activity, mutations in recB,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…A combination of recG and rnhA mutations is lethal In the course of our previous studies on possible roles of homologous recombination on cSDR Kogoma et al, 1994), we had attempted and failed to introduce, by P1 phage-mediated transduction, the recG285::kan mutation into rnhA224 mutants although we had been able to combine any other rec mutations with the rnhA224 mutation. This suggested that simultaneous loss of RecG and RNase HI activities is lethal to the cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of recG and rnhA mutations is lethal In the course of our previous studies on possible roles of homologous recombination on cSDR Kogoma et al, 1994), we had attempted and failed to introduce, by P1 phage-mediated transduction, the recG285::kan mutation into rnhA224 mutants although we had been able to combine any other rec mutations with the rnhA224 mutation. This suggested that simultaneous loss of RecG and RNase HI activities is lethal to the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we presented a model (Cao and Kogoma, 1993;Kogoma et al, 1994) which is radically different from the de novo formation model above. It is hypothesized that a persistent R-loop is formed by invasion of the duplex by a transcript that has just been synthesized and displaced from the template ( Figure 6B).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These results suggested that RecG, like RNase HI, plays an important role in the removal of R‐loops. R‐loops are thought to be required for the initiation of cSDR (Kogoma et al ., 1994; Hong et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriophage T4 has been shown, both in vivo (42) (21). Thus, it is extremely unlikely that cSDR involves homologous recombination.…”
mentioning
confidence: 99%